A review on the separation of molybdenum, tungsten, and vanadium from leach liquors of diverse resources by solvent extraction. Issue 5 (2nd September 2016) - Nguyen, Thi Hong; Lee, Man Seung
Abstract: Molybdenum, vanadium, and tungsten coexist with other valuable metals in diverse resources. In order to recover these metals with high purity, hydrometallurgical processes consisting of leaching followed by solvent extraction have been developed. The solvent extraction systems for the separation of Mo–V, Mo–W, and Mo–V–W from various aqueous medium were reviewed in this work. The aqueous chemistry of the three metals (Mo, V, and W) strongly depends on solution pH, metal concentration, and the nature of medium. On the basis of species of the three metals, the separation of these metals by solvent extraction with cationic and solvating extractants and amines were evaluated and the optimum conditions were reported. Cationic and solvating extractants are effective for the separation of molybdenum and vanadium from acidic solutions. Amines are found to be the most promising extractants for the separation of molybdenum and tungsten from alkaline solutions. However, the complete separation of the three metals by amines or solvating extractants is difficult from either acidic or alkaline solutions.